2006
DOI: 10.1007/11677482_2
|View full text |Cite
|
Sign up to set email alerts
|

Toward Adaptive Information Fusion in Multimodal Systems

Abstract: Multimodal contrastive learning train neural networks by levergaing data from heterogeneous sources such as images and text. Yet, many current multimodal learning architectures cannot generalize to an arbitrary number of modalities and need to be hand-constructed. We propose AutoBIND, a novel contrastive learning framework that can learn representations from an arbitrary number of modalites through graph optimization. We evaluate AutoBIND on Alzhiemer's disease detection because it has real-world medical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Integration patterns are also investigated in [3,4], were machine learning based approaches to predict a user's integration pattern were presented, based on the data of [7]. It is shown that 15 samples per user are enough to predict a user's integration pattern with an accuracy of 81%, so integration patterns can be detected relatively fast, even in an automated way.…”
Section: Related Workmentioning
confidence: 99%
“…Integration patterns are also investigated in [3,4], were machine learning based approaches to predict a user's integration pattern were presented, based on the data of [7]. It is shown that 15 samples per user are enough to predict a user's integration pattern with an accuracy of 81%, so integration patterns can be detected relatively fast, even in an automated way.…”
Section: Related Workmentioning
confidence: 99%
“…A novel trend of work investigates explicit integration of machine learning algorithms into the data collection process to accomplish adaptation. For example, machine learning methods are deployed in [36] to achieve on-line adaptation to users' multimodal temporal thresholds within a human computer interaction application framework. Some other work studies application of reinforcement learning to adaptive fusion systems to perform dynamic data reliability estimation [5,35].…”
Section: Related Workmentioning
confidence: 99%